Barack Obama and the Arab Spring a successful balancing act of foreign policy and diplomacy - Zohny, A. Y. (Ahmed Younis) (Lexington Books, 2021)
"In Barack Obama and the Arab Spring: A Successful Balancing Act of Foreign Policy and Diplomacy, Ahmed Y. Zohny develops a well-blended marriage of history and political theories of U.S. foreign policy, diplomacy, public diplomacy, and national security"--